Integration of Pastoral Counselling and Christian Leadership Spirituality In Addressing the Moral Degradation of Generation Z - Silaen, Riko (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract:The moral degradation of Generation Z poses a challenge for society and the church due to the increasing identity crisis, inconsistency with ethics, and even the weakening of spiritual orientation in their lives. This condition is exacerbated by rapid digital cultural changes, so that traditional Christian leadership mentoring patterns are no longer able to respond to the moral development needs of the younger generation. As a result, the church needs an integrative approach that combines pastoral counselling and Christian leadership spirituality to facilitate the formation of Christian character and values. This study aims to examine in depth the integration of pastoral counselling and Christian leadership spirituality as a relevant approach in addressing the moral degradation of Generation Z. It uses a qualitative-descriptive method with a literature study approach. The results show that the integration of pastoral counseling and Christian leadership spirituality provides a solid theological foundation for forming an assistance approach that holistically touches on the psychological and spiritual aspects of Generation Z. Through a deep understanding of the dynamics of moral degradation and the application of an integrative model that includes counselling, spiritual guidance, and leadership role models, the church obtains a relevant and transformative intervention pattern. The implementation of this model in church ministry enables the creation of sustainable moral restoration and the strengthening of the capacity of Christian leaders in guiding the younger generation to face the complexities of digital culture.